2016
DOI: 10.1155/2016/9095242
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Improves Vascular Calcification in Rats by Inhibiting Endoplasmic Reticulum Stress

Abstract: In this study, the vitamin D3 plus nicotine (VDN) model of rats was used to prove that H2S alleviates vascular calcification (VC) and phenotype transformation of vascular smooth muscle cells (VSMC). Besides, H2S can also inhibit endoplasmic reticulum stress (ERS) of calcified aortic tissues. The effect of H2S on alleviating VC and phenotype transformation of VSMC can be blocked by TM, while PBA also alleviated VC and phenotype transformation of VSMC that was similar to the effect of H2S. These results suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 35 publications
2
25
0
4
Order By: Relevance
“…Our and other studies have reported decreased content of H 2 S and protein levels of cystathionine γ-lyase, the primary enzyme contributing to production of H 2 S in the cardiovascular system, in rats with VC (Wu et al, 2006 ; Yang et al, 2016 ). Given that H 2 S facilitates the sensitivity of baroreflex both in normal rats and rats with VC, these results suggest that the decreased levels of endogenous H 2 S in VC may be mediated by impaired baroreflexive sensitivity.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Our and other studies have reported decreased content of H 2 S and protein levels of cystathionine γ-lyase, the primary enzyme contributing to production of H 2 S in the cardiovascular system, in rats with VC (Wu et al, 2006 ; Yang et al, 2016 ). Given that H 2 S facilitates the sensitivity of baroreflex both in normal rats and rats with VC, these results suggest that the decreased levels of endogenous H 2 S in VC may be mediated by impaired baroreflexive sensitivity.…”
Section: Discussionsupporting
confidence: 50%
“…A series of investigations have shown the ameliorative effect of H 2 S on VC (Wu et al, 2006 ; Zavaczki et al, 2011 ). We previously reported that H 2 S alleviated VC in rats by preventing ERS (Yang et al, 2016 ). Our current data further confirm that H 2 S treatment ameliorated VC and inhibited transformation of the VSMC phenotype and activation of ERS in both the aorta and carotid artery in rats.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, the ERS inducer Tm could block the ameliorated effect of H 2 S on VC, while the effect of the ER stress inhibitor PBA on VC in rats treated with vitamin D3 plus nicotine was similar as that of H 2 S.These indicated that H 2 S ameliorated VC by suppressing ERS. Moreover, the protein levels of phosphorylated AKT and Akt were both upregulated by H 2 S, suggesting that activation of the Akt signaling pathway is involved with the above effect of H 2 S [89]. With the development of research, it will provide a new strategy and target for the prevention and treatment of VC.…”
Section: H 2 S Influences Endoplasmic Reticulum Stress In Vascular DImentioning
confidence: 99%
“…Vitamin D3 plus nicotine (VDN) induces VC and phenotypic conversion of VSMC in rats. H 2 S may alleviate VC and VSMC phenotypic changes by reducing endoplasmic reticulum stress (ERS) ( Yang et al, 2016 ). In addition, NaHS enhances the expression of NADPH dehydrogenase 1 (NQO1) by enhancing nuclear factor (erythrocyte-derived 2)-like 2 (NRF2) activity, which in vitro attenuates calcineurin-induced calcification of VSMCs by cyclic troponin particles (CPP) ( Aghagolzadeh et al, 2017 ).…”
Section: H 2 S and Cardiovascular Diseasesmentioning
confidence: 99%